2015
DOI: 10.2752/089279315x14129350721812
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Randomized Controlled Trials of Animal-Assisted Therapy on Psychosocial Outcomes

Abstract: the use of animal-assisted interventions (aaIs) to achieve psychological benefits has expanded rapidly over the last few years. however, this is a vastly under-researched area, and the research to date has been largely descriptive, in the form of case studies, or has used only small groups of participants with no control condition. Remarkably few studies have utilized gold standard randomized controlled designs. the aim of the present review was to examine the current state of the literature in regard to only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 28 publications
2
70
0
8
Order By: Relevance
“…AAP can be considered a specific form of AAT. Several meta‐analyses (Nimer & Lundahl, ; Souter & Miller, ) and systematic reviews (Kamioka et al, ; Kendall et al, ; Maujean, Pepping, & Kendall, ; Rossetti & King, ) have concluded that AAT is a valuable resource in the field of clinical psychology and psychiatry. More specifically, evidence from randomized controlled trials indicates that AAT has a positive effect on a wide range of psychological and social factors in patients with psychological disorders (Maujean et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…AAP can be considered a specific form of AAT. Several meta‐analyses (Nimer & Lundahl, ; Souter & Miller, ) and systematic reviews (Kamioka et al, ; Kendall et al, ; Maujean, Pepping, & Kendall, ; Rossetti & King, ) have concluded that AAT is a valuable resource in the field of clinical psychology and psychiatry. More specifically, evidence from randomized controlled trials indicates that AAT has a positive effect on a wide range of psychological and social factors in patients with psychological disorders (Maujean et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…From Autistic Spectrum Disorders (Kern et al, 2011;O 'Haire, 2013) to severe mental illness (Barker & Dawson, 1998;Kamioka et al, 2014;Maujean et al, 2015;Wisdom et al, 2009), the literature increasingly indicates there is value in the facilitation of human-animal contact within interdisciplinary clinical practice. This therapeutic framework has resulted in the use of terms such as ''pet therapy'', ''animal-assisted therapy'' and ''animal-assisted activities'', referring to a reciprocal dynamic between humans and animals which addresses ''physical and/or emotional needs'' (Adams, 2010;Carmack, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The first posits that EAT provides a positive context for psychological growth. The second hypothesis argues that the horse has therapeutic qualities that can lead to unique psychological changes that would not otherwise occur (Maujean et al 2013, Kendall et al 2014, Maujean et al 2015. It is this final point that proponents of EAT argue horses have unique therapeutic potential.…”
Section: Equine-assisted Therapymentioning
confidence: 99%
“…, Maujean et al . ). It is this final point that proponents of EAT argue horses have unique therapeutic potential.…”
Section: Introductionmentioning
confidence: 97%